THE STUDENTS ATTITUDE TO SCIENCE - KRPÁLKOVÁ KRELOVÁ, Katarína; TÓBLOVÁ, Eva (Trends in education, 2008)
The article is aimed to attitude of students to science. We show the aim and intermediate results of research. The research was realised in chosen comprehensive schools.
Keywords: science; research; motivation